A carbon nanoparticles‐based solid‐phase purification method facilitating sensitive MALDI–MS analysis of permethylated N‐glycans. Issue 24 (6th September 2018) - Zhong, Jieqiang; Banazadeh, Alireza; Peng, Wenjing; Mechref, Yehia
Abstract: In recent decades, MALDI–MS has been extensively used for the analysis of glycans. However, native glycans usually have low ionization efficiency in MS, which hinders the direct analysis. Permethylation of glycans is a solution for this issue, but a significant amount of salt is introduced during this process, which can further suppress the MS signals. Thus, it is necessary to purify the glycans prior to MALDI–MS analysis. In this study, we developed a carbon nanoparticles‐based solid‐phase purification method to enable direct MALDI–MS analysis of permethylated glycans. Two carbon nanomaterials, carbon nanoparticles (CNPs) and graphene nanosheets (GNs), and two conventional carbon materials, activated charcoal and porous graphitic carbon (PGC), were investigated as sorbents to purify permethylated N ‐glycans derived from ribonuclease B and fetuin. The results confirmed the superior performance of CNPs over the other carbon materials. Additionally, our method was also employed to purify glycans released from human sera in different esophageal disease stages. The obtained data confirmed 16 and 18 structures in adenocarcinoma and Barret's sera with significantly different relative intensities versus disease‐free sera. Comparing the performance of CNPs‐based solid‐phase purification method employed in this study to online purification suggested more than 97% recovery rate. The results of this study demonstrate that CNPs have the potential to be a better alternative to existing solid‐phase purification sorbents.